A study of an association between peripheral neuropathy and cognitive impairment in Type 2 Diabetes Mellitus patients - Nair, V. Rubini (2020)
Type 2 Diabetes Mellitus (DM) is a chronic disease with many complications. Among the well-known complications are nephropathy, neuropathy, and retinopathy. A complication which is rarely looked upon is cognitive impairment which is recently being highly associated with diabetes mellitus. There are a few recent publications which revealed that cognitive impairment and peripheral neuropathy could be brought about by a similar pathophysiology. A total of 279 diabetes mellitus patients were recruited from a diabetes clinic in Hospital Universiti Sains Malaysia from the 1st of July, 2018 until the 30th of September, 2019. Demographic, clinical and laboratory data were recorded from the patients’ file. Cognitive impairment was assessed by the Montreal Cognitive Assessment (MOCA) and peripheral neuropathy was assessed by Michigan Neuropathy Screening Instrument (MNSI). The association between peripheral neuropathy and cognitive impairment was analysed using simple and multiple logistic regression method. A total of 279 patients were included in this study. The mean age of the patients was 62.38 (SD 8.53) years old. The mean duration of diabetes mellitus was 9.59 (SD 5.53) years. Majority of them were females, n=206 (73.8%). All of them were married and 97.5% were Malays. 183 patients (65.6%) had peripheral neuropathy while 196 patients (70.3%) experienced cognitive impairment. There was a significant association between peripheral neuropathy and cognitive impairment (p<0.001). Half of the patients with peripheral neuropathy had concomitantcognitive impairment (n=141, 50.5%). There was also a significant association of gender in which females conferred 74% lower odds to experience cognitive impairment compared to males (p<0.001). For patients with hyperlipidaemia, there were 2.07 times odds to experience cognitive impairment as compared to patients without hyperlipidaemia (p=0.046). For patients with retinopathy, there were 2.14 times odds to experience cognitive impairment as compared to patients without retinopathy (p=0.008). There was a significant association between the development of cognitive impairment among diabetes mellitus patients with a peripheral neuropathy. Female gender was associated with lower risk of cognitive impairment as compared to male. DM patients with dyslipidaemia and diabetic retinopathy have a higher risk of developing cognitive impairment.